Institution for the Use of Groundwater in Assam: A Study of Groundwater Markets with Special Emphasison Structure, Determinants, Reliability and Efficiency - Tamuli, Jitu (My University, 2014)
Expansion of groundwater based irrigation technology has facilitated the emergence of institutions like groundwater market or water market in some states of India including Assam which lies in Eastern India with abundant groundwater reserves and heavy monsoon precipitation ensuring easy replenishment. In view of the fact that small and marginal farmers dominate the agricultural scenario of the state with limited capability for capital investment, expansion of groundwater markets is thus, considered as an alternative institution which can ensure equity in access to irrigation across farmers. However, due to the residual nature of the market, the buyers may be subject to inadequate water supply resulting in differences in the attainment of technical efficiency of the farmers under different structures of the market. With this backdrop, the study has been conducted to examine the nature, structure and functioning of groundwater markets in the state; to identify determinants of groundwater markets; to examine the issue of reliability and the factors affecting reliability of the market; and to examine technical efficiency across the farmers under different structures of the market. Both secondary and primary data are used to carry out the study. Secondary data have been used mainly to examine the status of groundwater based irrigation development in the state. In order to examine the issues of groundwater markets, the study has mainly used primary data collected from 198 respondents from two districts of Assam, viz. Nagaon and Morigaon which constitutes the Central Brahmaputra Valley Zone (CBVZ) of the state. The nature and structure of the market, characteristics of tubewells and underlying production system of the crop undertaken have been examined using simple statistical tools like percentage, ratio, average, etc. The determinants of tubewell ownership, water buying and selling decisions of a farmer and the determinants of reliability of the market have been examined using the logit regression model. The Stochastic Frontier Approach (SFA) is used to estimate technical efficiency scores on a farmer plot. The variation in the farm specific technical efficiency is obtained by modeling technical inefficiency as a function of some of the farm-specific characteristics.
Dutta, Mrinal Kanti
Keywords: HUMANITIES AND SOCIAL SCIENCES